What do we know about Cooperative Compliance? Insights from Literature Review in Transfer Pricing Supervision - Supriyadi (Yayasan Ilomata, 2024)
Cooperative compliance is often defined as a framework for trust-based relationships in which tax authorities and taxpayers work together to establish and uphold mutual understanding. The main reported areas of tax compliance risks and disputes in Indonesia include profit shifting and transfer pricing. Through a literature review, we attempt a stocktake of the cooperative compliance literature in this review about transfer pricing supervision. A comprehensive literature search identified 17 studies published between 2014 and 2023. Two key types of interventions were identified: cooperative compliance and transfer pricing supervision. According to the review's findings, cooperative compliance research should focus more on using cooperative compliance as a strategic tool in business than just on tax compliance. This evaluation concludes with recommendations for future cooperative compliance research.